2000
DOI: 10.1021/jf0003092
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Dibenzo-p-dioxin and Dibenzofuran Concentrations in Beef Animals from a Feeding Study

Abstract: Four calves were fed polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans for 120 days at levels somewhat higher than what may be found in forage near some waste incinerators and manufacturing plants. Four calves were fed identical diets but without the chemicals. Using bioelectrical impedance measurements of total body fat, 30-50% of the dosed 2,3,7,8-TCDD, 1,2,3,7,8-PeCDD, and 2,3,4,7,8-PeCDF was estimated to be retained by the animals. Although these same congeners were bioconcentrated in adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 30 publications
2
32
2
Order By: Relevance
“…It has been seen that exposure to pentachlorophenol (PCP)-treated wood produced a distinctive residue pattern in animals (Fries et al 1999, Feil et al 2000. This pattern showed little or no tetra-or penta-congeners but high amounts of 1,2,3,6,7,8-HxCDD, 1,2,3,4,6,7,8-HpCDD and OCDD (figure 3), somewhat resembling the PCP formulation used to treat the wood.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been seen that exposure to pentachlorophenol (PCP)-treated wood produced a distinctive residue pattern in animals (Fries et al 1999, Feil et al 2000. This pattern showed little or no tetra-or penta-congeners but high amounts of 1,2,3,6,7,8-HxCDD, 1,2,3,4,6,7,8-HpCDD and OCDD (figure 3), somewhat resembling the PCP formulation used to treat the wood.…”
Section: Resultsmentioning
confidence: 96%
“…One station (Las Cruces, NM) submitted only serum samples. Because it was found that serum dioxin levels in cattle did not always correlate with adipose tissue levels on a lipid-weight basis (Feil et al 2000, Huwe et al 2001) and because most congeners were near the limits of detection (58% below background levels), the serum collected was not included. The early analyses for this study (done in 1995) represent the first dioxin analyses performed at our laboratory and showed higher than desired levels of background contamination in the blanks (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This was the source of the dioxins in the feed additive choline chloride in 2000, which was mixed with sawdust contaminated with PCP (Llerena, Abad, Caixach, & Rivera, 2003). It was also the source in stables where PCP-treated wood was used as building material (Feil et al, 2000;Fries, Veil, Zaylskie, Bialek, & Rice, 2002) and in a case in Italy with contaminated wood shavings used as bedding in chicken farms (Brambilla, Fochi, De Filippis, Iacovella, & di Domenico, 2009;Diletti, Ceci, De Massis, Scortichini, & Migliorati, 2005). The latter is of interest regarding new EUlegislation on animal husbandry, including provision of bedding like wood chips.…”
Section: Feed Incidentsmentioning
confidence: 99%
“…Pentachlorophenol treated wood in itself has also proven to be a source of dioxins and dibenzofurans in products of animal origin, especially milk and body fat of calves. (Fries et al, 1999); (Feil et al, 2000). Poultry that is provided with wood to increase their welfare might therefore pick up traces of dioxins or dibenzofurans, if this wood happens to be treated with chlorine containing compounds.…”
Section: Dioxins and Dibenzofurans In The Environment And The Productmentioning
confidence: 99%